Sustainable Livelihood Strategies of Farmer Groups in the Food Security Program of Kute Siantan - Majid, Tuzhara Ramadhanty (Amalee: Indonesian Journal of Community Research and Engagement, 2025)
The Food Security Program in Kute Siantan District, Anambas Islands Regency, is a form of Corporate Social Responsibility (CSR) by Medco E&P Natuna Ltd. in support of Sustainable Development Goal (SDG) 2. This program aims to reduce the community's dependence on food supplies from outside the region by strengthening the capacity of local farmers in vegetable production. This study aims to analyze the livelihood capital of the community to formulate a sustainable livelihood strategy for farmer groups. The research employs a qualitative approach, utilizing ethnographic methods and document studies, which were conducted over approximately two months, from February to April 2025. Data were collected through participatory observation and in-depth interviews with 21 informants, comprising farmers, program assistants, and village officials. The results of the study indicate that farmers possess five main forms of capital: human, natural, social, physical, and financial capital, which still face numerous sustainability challenges. Based on the analysis, five strengthening strategies are recommended, namely: (1) determination of key farmers through measurable assessments to reduce dependence on companions; (2) the use of abandoned land and local organic matter as an alternative to inorganic fertilizers; (3) strengthening the value of cooperation in the activities of farmer groups; (4) maintenance and management of agricultural equipment collectively; and (5) market expansion and diversification of agricultural products. The strengthening of the five capitals is the foundation for the sustainable livelihood strategy of farmer groups, supporting the sustainability of the Food Security Program beyond the end of the CSR intervention.